The application of the New Zealand Civil Aviation Rule Part 115 for the regulation of adventure aviation activities : dissertation submitted in partial fulfillment for the degree of Master of Aviation Management, Department of Aviation, Massey University - Marriott, David (Massey University, 2011)
Research was undertaken to examine the implementation requirements of a proposed rule, NZCAR Part 115,which has been developed with the intention to regulate “adventure aviation” activities in New Zealand. The regulation applies to a wide range of tourism focused airborne operations including the use of ex-military and aerobatic aircraft for joyriding, passenger flights in balloons, gliders, tandem parachuting and hang-gliding operations. The rule was considered necessary as there has been a lack of any recognized safety standards applicable to these activities when they are conducted beyond a purely recreational purpose. An increasing number of operators commercialise their activities by focusing on taking passengers for rides as opposed to conducting training or “trial flights” (which are assumed to be for the purpose of introducing people to the sport). Many of these operations use non-certified aircraft which have not been intended for the carriage passengers on a commercial scale. Where paying passengers are carried, safety is assumed to require a greater level of management. The regulator – the New Zealand Civil Aviation Authority - considers that a formal system that applies standards similar to those of small airline would be more appropriate. A new rule was required due to the novel and diverse nature of activities, and the various types of aircraft used. Specialist legislation for adventure aviation would also open up the sector for further commercial opportunities and would provide the ability to regulate such activities within the civil aviation system. The thesis includes a review of literature which examines the basis of the legislatory requirements and defines the rationale for the rule-making standard, as well as introducing notions for defining and assessing risk within aviation. The review also looks at published industry reaction to the development of the Rule. A part of the research, the survey of operators, elicits their opinion as to the workability of the new legislation. The survey also tests the current level of each operator’s compliance according to a 72 point checklist of operational items and ascertains what modifications to the systems and practices are required in order to comply. The research outcomes identified two groups of operators - one of which has standards and systems that are close to compliance with the new legislation and the other for which compliance would be difficult due to deficient systems and practices. Analysis of the differences highlighted a cultural separation of the groups in terms of their connection with mainstream general aviation and their understanding of the risk management concepts and practices required for commercial operations. The discussion of the results of the research highlights problems with the application of the proposed regulation, particularly to the non-compliant group. Issues include the recreational origins of the sector, a lack of acceptance of the Rule by operators, and on-going problems with the consultation and collaboration in the rule-development process. Workable compliance strategies and processes are discussed, including developing an ecological approach to managing safety as part of best practice. Recommendations look at possible strategies for implementation including the requirement for more pro-active education and enculturation processes, and the formation of a national representative body
Keywords: New Zealand Civil Aviation Division; Rules; Regulations; Recreational aviation; Law and legislation; Safety measures; Aeronautics; New Zealand